77.3k views
1 vote
Writing Simplify this expression. Assume that z is nonzero. Use pencil and paper. Describe howthe values of the expression vary with the values chosen for z.

Writing Simplify this expression. Assume that z is nonzero. Use pencil and paper. Describe-example-1

1 Answer

2 votes
Answer:
5z^0=\text{ 5}Explanations:

The given expression is:


5z^0

Note that any number (except 0) raised to the power of zero, will give us 1

Since z is a non zero number, let us assume z = -1, 1, 2 and see the resulting value of the expression.


\begin{gathered} 5z^0 \\ \text{When z = -1} \\ 5(-1)^0\text{ = 5(1) = 5} \\ \text{When z = 1} \\ 5(1)^0\text{ = 5(1) = 5} \\ \text{when z = 2} \\ 5(2)^0=\text{ 5(1) = 5} \\ Therefore,\text{ for all nonzero values of z} \\ z^0=1 \\ 5z^0=\text{ 5}*1\text{ = 5} \end{gathered}

User Ulab
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.